Policy Note on Population Growth and its Implications in Timor-Leste - World Bank (Washington, DC, 2014)
The report offers a description of current demographics, including density, population structure, and the components of population change. It explains projection procedures and provides results, including some alternative projections. The report assesses consequences of population growth for key sectors of society such as education and employment and offers options for modifying future population trends, focusing on high fertility and the reasons behind it. A brief discussion of the health sector highlights problems of promoting family planning. Comparisons are made where appropriate with other developing countries, particularly within Southeast Asia.